PENGARUH CURRENT RATIO, DEBT TO ASSET RATIO DAN TOTAL ASSET TURN OVER TERHADAP NET PROFIT MARGIN - Lumbantobing, Sabar Pardamean; Adwimurti, Yudhistira; Selfiani, Selfiani (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2023)
This research investigates the impact of financial ratios, including Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turn Over (TATO), on Net Profit Margin (NPM) in mining companies listed on the Indonesia Stock Exchange for the period 2017-2021. The study aims to assess both the individual and collective influence of these financial indicators on the NPM of the selected companies. Data for the analysis were sourced from www.hots.mirraeasset.co.id, with a total population of 49 companies. However, only 31 companies met the specified sample criteria. The research employs a multiple linear regression technique, facilitated by the SPSS version 25.0 application. The findings reveal that, individually, the Current Ratio has no significant impact on the Net Profit Margin, while the Debt to Asset Ratio exhibits a significant influence. On the other hand, Total Asset Turn Over has no significant effect on the Net Profit Margin when considered individually. Nevertheless, when assessed collectively, the Current Ratio, Debt to Asset Ratio, and Total Asset Turn Over jointly demonstrate a significant impact on the Net Profit Margin. It is noteworthy that, among these variables, none establishes a close relationship with the Net Profit Margin.